Practical guide to the care of the medical patient (Mosby Yearbook, 1991)
This book combines relevant clinical, therapeutic and laboratory data in a convenient reference package. The guide covers 160 common medical topics, 220 of the most frequently prescribed medications, as well as interpretations of approximately 150 laboratory tests.